Religious Moderation Through Arabic Language References For Religious Courses Of State Islamic Universities - Ali, Nur; Afwadzi, Benny; Kholid, Abd (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Religious moderation, believed to be the solution to radicalism in Indonesia, has a real obstacle in terms of a tendency to use English language references. Meanwhile, they are considered to be full of liberalization and pro-Western politics. This research examined the insertion of religious moderation through Arabic language references. It aimed to offer religious moderation with more comprehensive Arabic religious references on religious materials. The research was qualitative and used a case study method. The subjects were nine lecturers and seven students from the Faculty of Tarbiyah and Teacher Training, UIN Malang, who were selected purposively. The research found that religious moderation was inserted into the religious material through CLO, teaching materials with original Arabic texts, and the learning process. The three insertion models were chosen to follow instructions from university leaders, introduce the terminology of religious moderation from Arabic and non-Arabic language references, and ground religious moderation among students. Besides, using original Arabic text references is quite effective and grows students' confidence. This research suggested that when inserting religious moderation, especially at PTKI, we should include Arabic references because it has been proven to increase students' confidence effectively.